2022
DOI: 10.1111/jocs.17005
|View full text |Cite
|
Sign up to set email alerts
|

Erector spinae plane block as perioperative analgesia for midline sternotomy in cardiac surgery: A systematic review and meta‐analysis

Abstract: Background: Inadequate analgesia following cardiac surgery increases postoperative complications. Opioid-based analgesia is associated with side effects that may compromise postoperative recovery. Regional anesthetic techniques provide an alternative thereby reducing opioid requirements and potentially enhancing postoperative recovery. The erector spinae plane block has been used in multiple surgical procedures including sternotomy for cardiac surgery. We, therefore, aimed to characterize the impact of this bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…ESP block provides analgesia to the posterior and anterolateral hemithorax by blocking the posterior and anterior rami. Coverage of the anteromedial hemithorax is unreliable 57 . Local anaesthetic injection into the fascial plane between the thoracic transverse processes and the erector spinae muscle typically results in a T2–T9 block on the ipsilateral side.…”
Section: Erector Spinae Plane Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…ESP block provides analgesia to the posterior and anterolateral hemithorax by blocking the posterior and anterior rami. Coverage of the anteromedial hemithorax is unreliable 57 . Local anaesthetic injection into the fascial plane between the thoracic transverse processes and the erector spinae muscle typically results in a T2–T9 block on the ipsilateral side.…”
Section: Erector Spinae Plane Blockmentioning
confidence: 99%
“…Coverage of the anteromedial hemithorax is unreliable. 57 Local anaesthetic injection into the fascial plane between the thoracic transverse processes and the erector spinae muscle typically results in a T2-T9 block on the ipsilateral side. The advantages of ESP block include technical simplicity, direct ultrasound visualisation and possibly less hypotension.…”
Section: Intercostal Nerve Block and Cryoablationmentioning
confidence: 99%
“…They report no difference in postoperative pain scores, intraoperative opioids, time to extubation, and intensive care unit (ICU) length of stay in patients receiving ESPB versus no ESPB. 1…”
mentioning
confidence: 99%
“…Additional limitations to this study exist. With regard to the validity of the meta‐analysis, forest plots in the King et al 1 analysis do not appear to be weighted for sample size. The authors do accurately identify high levels of heterogeneity with I 2 > 90% for all outcomes they examined, however, this does not remedy this limitation, and it could be argued that these studies should not have been combined in a meta‐analysis and instead reported in a narrative review 17 .…”
mentioning
confidence: 99%
See 1 more Smart Citation